2021
DOI: 10.1038/s41598-021-91398-7
|View full text |Cite
|
Sign up to set email alerts
|

Electricity-producing Staphylococcus epidermidis counteracts Cutibacterium acnes

Abstract: Staphylococcus epidermidis (S. epidermidis) ATCC 12228 was incubated with 2% polyethylene glycol (PEG)-8 Laurate to yield electricity which was measured by a voltage difference between electrodes. Production of electron was validated by a Ferrozine assay. The anti-Cutibacterium acnes (C. acnes) activity of electrogenic S. epidermidis was assessed in vitro and in vivo. The voltage change (~ 4.4 mV) reached a peak 60 min after pipetting S. epidermidis plus 2% PEG-8 Laurate onto anodes. The electricity produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Increasing evidence showed that an interaction between Staphylococcus epidermidis and Cutibacterium acne could be involved with the physiopathology of acne. 39,40 A study has shown that Staphylococcus epidermidis isolated from the skin can inhibit the overgrowth of Cutibacterium acne by fermenting glycerol. 41 On the contrary, Cutibacterium acne can also influence the biofilm formation of Staphylococcus epidermidis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence showed that an interaction between Staphylococcus epidermidis and Cutibacterium acne could be involved with the physiopathology of acne. 39,40 A study has shown that Staphylococcus epidermidis isolated from the skin can inhibit the overgrowth of Cutibacterium acne by fermenting glycerol. 41 On the contrary, Cutibacterium acne can also influence the biofilm formation of Staphylococcus epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our observation that Cutibacterium remained at high levels in skin pores, whereas its dominance on the skin surface was replaced by Staphylococcus which grows better when the oxygen level is higher. Increasing evidence showed that an interaction between Staphylococcus epidermidis and Cutibacterium acne could be involved with the physiopathology of acne 39,40 . A study has shown that Staphylococcus epidermidis isolated from the skin can inhibit the overgrowth of Cutibacterium acne by fermenting glycerol 41 .…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that S. epidermidis can ferment glycerol and PEG-8 laurate to generate potential electron donors for electricity generation to combat ultraviolet damage 30 or suppress acne vulgaris 31 . In this study, we further demonstrated that adding glucose to the culture medium of B. circulans in vitro can inhibit the growth of C. acnes ; specifically, this suppression was significantly reversed when roseoflavin was added to the mix.…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis and S. hominis have been shown to secrete antimicrobial peptides that kill S. aureus, and transplantation of these species onto the skin of patients with atopic dermatitis leads to decreased colonization by S. aureus [23]. It has been also reported that butyric acid from S. epidermidis down-regulates the ultraviolet-induced pro-inflammatory IL-6 cytokine [24] and that the electricity produced by S. epidermidis caused significant growth attenuation and cell lysis of P. acnes [25]. Thus, robustness in the quantity of each microbiota might support microbe-microbe interactions between Staphylococcus species that are beneficial to the host.…”
Section: Discussionmentioning
confidence: 99%